Gut Microbiota Variations between Henoch-Schonlein Purpura and Henoch-Schonlein Purpura Nephritis - Fang Zhou; Qimin Shao; Lihong Jia; Chunyan Cai (Gastroenterology Research and Practice)
Background. In China, little is known regarding the differences between children with Henoch-Schonlein purpura (HSP) and Henoch-Schonlein purpura nephritis (HSPN) concerning their gut microbiota. Methods. We recruited 25 children with HSP, 25 children with HSPN, and 25 healthy children to investigate the differences. Fecal samples were collected and analyzed by sequencing the V3-V4 region of the 16S rRNA gene. The diversity of the fecal gut microbiota was compared between the patient groups. Results. Rarefaction curves showed that the gut microbial diversity between the three groups differed significantly (P=0.0224). The top five most abundant gut microbial genera were Bacteroides, Faecalibacterium, Prevotella, Ruminococcaceae, and Megamonas in children with HSP; Bacteroides, Faecalibacterium, Prevotella, Bifidobacterium, and Ruminococcaceae in children with HSPN; and Bacteroides, Prevotella, Faecalibacterium, Ruminococcaceae, and Bifidobacterium in healthy children. Children with HSP had the lowest Bifidobacterium abundance among the three groups (P<0.05). Children with HSPN had a lower abundance of Akkermansia than children with HSP (P<0.05), whereas children with HSPN had a higher Alistipes abundance than children with HSP (P<0.05). Fecal microbial community composition did not differ significantly between groups (ANOSIM, R=−0.002, P=0.46). Despite the small sample size, our results indicate that children with HSP or HSPN displayed dysbiosis of the gut microbiota. Conclusion. This study provides valuable insights that will benefit the development of future microbe-based therapies to improve clinical outcomes or prevent the incidence of HSP or HSPN in children.